2010
DOI: 10.1016/j.rbmo.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

GnRH agonist and GnRH antagonist protocols in ovarian stimulation: differential regulation pathway of aromatase expression in human granulosa cells

Abstract: Gonadotrophin-releasing hormone (GnRH) agonists and antagonists have been widely used to prevent premature LH surge during ovarian stimulation. However, studies have shown a significantly lower serum oestradiol concentration on the day of human chorionic gonadotrophin administration for cycles using GnRH antagonist. This study compared aromatase gene expression in granulosa lutein cells from 50 women randomly assigned to receive either GnRH agonist (group 1, n=28) or GnRH antagonist (group 2, n=22). The cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
2
19
0
3
Order By: Relevance
“…Accumulating evidence indicates that GnRH-ant can inhibit dose-dependently aromatase expression and activity in human granulosa cell [33,34]. Remarkably, these findings correlate well with the clinical evidence that GnRhant are associated with lower estradiol levels in both serum and follicular fluid.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Accumulating evidence indicates that GnRH-ant can inhibit dose-dependently aromatase expression and activity in human granulosa cell [33,34]. Remarkably, these findings correlate well with the clinical evidence that GnRhant are associated with lower estradiol levels in both serum and follicular fluid.…”
Section: Resultssupporting
confidence: 70%
“…These data lead to the suggestion that both analogues do not substantially affect gonadotropin receptor status of granulosa cells, but that GnRH-ant can induce inhibitory effects on granulosa lutein cell aromatase activity. In line with the concept that ovarian steroidogenesis can be affected by GnRH-ant, Kalaf et al [33] found a significant reduction in serum estradiol concentrations in patients treated with GnRH-ant in comparison with those receiving GnRHa. The decrease in circulating concentrations of estradiol observable in the GnRH-ant patients, according to authors, could reflect a lower estradiol synthesizing capability of the GnRH-ant-exposed follicles.…”
Section: Gnrh-ant and Ovarian Steroidogenesismentioning
confidence: 81%
“…162 When follicular dynamics were compared between GnRHa and GnRH-antagonist cycles, it was found that the modulation of the FSH-induced protein kinase A pathway by protein kinase C was different in agonist versus antagonist cycles. 163 The changed modulation of this pathway results in lower levels of serum and follicular estradiol via lower levels of aromatase activity. It does not appear, however, that low levels of estradiol are, in fact, detrimental to pregnancy rates in these IVF cycles.…”
Section: Gnrh-agonist Down-regulation Regimensmentioning
confidence: 99%
“…The same happened in our case, the fourth initial attempts were conducted under the long agonist protocol. At the biochemical level, granulose lutein cells have showed a different pathway modulation of the FHS-induced kinases in agonist versus antagonist cycles [27]; hence it is logical to assume that the type of protocol may influence intrafollicular environment and oocyte maturation pathways and may contribute in some cases to abnormal oocyte development. However, other findings challenge this hypothesis, for example EFS cases are described in both agonist and antagonist protocols and also when GnRHa are used for triggering [3].…”
Section: Case Reportmentioning
confidence: 99%